Highly transparent and color-adjustable Eu2+ doped SrO-SiO2-Al2O3 multilayered glass ceramic prepared by controlling crystallization from glass. Issue 13 (October 2019) - Qiang, Yaochun; Pan, Zhifang; Liang, Mingzhang; Xu, Jianfei; Ye, Xinyu; Xia, Libin; You, Weixiong; Fu, Junxiang; Ming, Hong
Abstract: Multilayered inorganic transparent materials have been widely used as laser materials, scintillators and phosphors due to their excellent combined properties or functions. However, owing to the limitation of the current preparation technology, only the ceramics with cubic crystal structure could be fabricated into multilayered transparent materials, which has greatly obstructed the diversity of multilayered transparent materials. Here we report a novel non-cubic multilayered transparent phosphor with a ceramic/glass/ceramic sandwich-like structure prepared by controlling crystallization from Eu2 O3 -SrO-Al2 O3 -SiO2 bulk glass. The ceramic thicknesses, total transmittances, emission colors and the fluorescence quantum yields of the samples can be adjusted continuously within a certain range. The multilayered transparent phosphor could be used as a potential candidate for the white LEDs with high color rendering index. It can be anticipated that the controlled crystallization from bulk glass method is a simple, fast, cost-effective and promising synthesis approach to prepare non-cubic transparent materials with ceramic/glass/ceramic structures.